A novel technique of detecting MRI‐negative lesion in focal symptomatic epilepsy: Intraoperative ShearWave Elastography. Issue 4 (1st March 2014) - Chan, Huan Wee; Pressler, Ronit; Uff, Christopher; Gunny, Roxanna; St Piers, Kelly; Cross, Helen; Bamber, Jeffrey; Dorward, Neil; Harkness, William; Chakraborty, Aabir
Summary Focal symptomatic epilepsy is the most common form of epilepsy that can often be cured with surgery. A small proportion of patients with focal symptomatic epilepsy do not have identifiable lesions on magnetic resonance imaging (MRI). The most common pathology in this group is type II focal cortical dysplasia (FCD), which is a subtype of malformative brain lesion associated with medication‐resistant epilepsy. We present a patient with MRI‐negative focal symptomatic epilepsy who underwent invasive electrode recordings. At the time of surgery, a novel ultrasound‐based technique called ShearWave Elastography (SWE) was performed. A 0.5 cc lesion was demonstrated on SWE but was absent on B‐mode ultrasound and 3‐T MRI. Electroencephalography (EEG), positron emission tomography (PET), and magnetoencephalography (MEG) scans demonstrated an abnormality in the right frontal region. On the basis of this finding, a depth electrode was implanted into the lesion. Surgical resection and histology confirmed the lesion to be type IIb FCD. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.